Mesitylene-cored glucoside amphiphiles (MGAs) for membrane protein studies: importance of alkyl chain density in detergent efficacy. - Cho,KH; Ribeiro,O; Du,Y; Tikhonova,E; Mortensen,JS; Markham,K; Hariharan,P; Loland,CJ; Guan,L; Kobilka,BK; Byrne,B; Chae,PS (Chemistry - A European Journal, 2016)
Detergents serve as useful tools for membrane protein structural and functional studies. Their amphipathic nature allows detergents to associate with the hydrophobic regions of membrane proteins whilst maintaining the proteins in aqueous solution. However, widely used conventional detergents are limited in their ability to maintain the structural integrity of membrane proteins and thus there are major efforts underway to develop novel agents with improved properties. We prepared mesitylene-cored glucoside amphiphiles (MGAs) with three alkyl chains and compared these agents with previously developed xylene-linked maltoside agents (XMAs) with two alkyl chains and a conventional detergent (DDM). When these agents were evaluated for four membrane proteins including a G protein-coupled receptor (GPCR), some agents such as MGA-C13 and MGA-C14 resulted in markedly enhanced stability of membrane proteins compared to both DDM and the XMAs. This favourable behaviour is due likely to the increased hydrophobic density provided by the extra alkyl chain. Thus, this study not only describes new glucoside agents with potential for membrane protein research, but also introduces a new detergent design principle for future development.